"114"‐Type Nitrides LnAl(Si4−xAlx)N7Oδ with Unusual [AlN6] Octahedral Coordination. (28th February 2017) - Huang, Saifang; Huang, Zhaohui; Cao, Peng; Zujovic, Zoran; Price, Jason R.; Avdeev, Maxim; Que, Meidan; Suzuki, Furitsu; Kido, Tsuyoshi; Ouyang, Xin; Kaji, Hironori; Fang, Minghao; et al.
Abstract: Aluminum–nitrogen six‐fold octahedral coordination, [AlN6 ], is unusual and has only been seen in the high‐pressure rocksalt‐type aluminum nitride or some complex compounds. Herein we report novel nitrides LnAl(Si4− x Alx )N7 O δ (Ln=La, Sm), the first inorganic compounds with [AlN6 ] coordination prepared via non‐high‐pressure synthesis. Structure refinements of neutron powder diffraction and single‐crystal X‐ray diffraction data show that these compounds crystallize in the hexagonal Swedenborgite structure type with P 63 mc symmetry where Ln and Al atoms locate in anticuboctahedral and octahedral interstitials, respectively, between the triangular and Kagomé layers of [SiN4 ] tetrahedra. Solid‐state NMR data of high‐purity La‐114 powders confirm the unusual [AlN6 ] coordination. These compounds are the first examples of the "33‐114" sub‐type in the "114" family. The additional site for over‐stoichiometric oxygen in the structure of 114‐type compounds was also identified.